Current noise geometrically generated by a driven magnet - Tim Ludwig; Igor S. Burmistrov; Yuval Gefen; Alexander Shnirman (Physical Review Research, 2020)
We consider a nonequilibrium cross-response phenomenon, where a driven magnetization gives rise to electric shot noise (but no d.c. current). This effect is realized on a nanoscale, with a small metallic ferromagnet which is tunnel coupled to two normal metal leads. The driving gives rise to a precessing magnetization. The geometrically generated noise is related to a nonequilibrium electron distribution in the ferromagnet. Our protocol provides a channel for detecting and characterizing ferromagnetic resonance.